Pengaruh Bahan Pengemas terhadap Mutu Beras Padi Aromatik selama Penyimpanan - Jumali, Jumali; Indrasari, S. Dewi; Kusbiantoro, Bram (Jurnal Penelitian Pertanian Tanaman Pangan, 2011)
Research on the effect of packaging material for aromatic rice quality and its life storage was carried out. The aromatic rice varieties i.e Pandanwangi, Sintanur and Mentikwangi (each 750 kg) were dried in box dryer at 45oC for 12 hours. The dried paddy was milled at commercial milling to produce milled rice. The milled rice then were packed in high density polypropylene (HDPP), super bag and plastic sac. Factorial treatments were arranged in a completely randomized design, replicated thrice. The first factor was aromatic rice varieties (Sintanur, Mentikwangi and Pandanwangi) and the second factor was packaging material (superbag, high density polypropylene (HDPP) and plastic sac). Each treatment consisted of 5-7 kg of milled rice, kept in the room condition for six months. The physical, chemical characteristic, organoleptic test, and flavor composition were observed at the beginning, the middle and the end of storage. The result showed that physical quality of rice decreased parallel with the duration of storage. The whiteness, transparency and milling degree of rice kernel decreased as the period of storage increased. The infestation of insect in storage was found at 60 days after storing (at the second month) and tended to decrease parallel with insect life cycle. The used of plastic sac as packaging was invested by insect more than those of super bag and high density polypropylene. Therefore plastic sac was not recommended for packaging of aromatic rice at room condition. Organoleptic test indicated that cooked quality of aromatic rice decreased parallel with storing time. Based on colour, aroma, taste and texture, aromatic rice should be consumed within 90 days. After 90 days, the colour, aroma, taste and texture of the cooked rice was less preferred by panelis. The uses of plastic sac to pack aromatic rice produced cooked rice less preferable than those of super bag and high density polypropylene plastic.